Thrombotic Thrombocytopenic Purpura Associated with Pneumococcal Sepsis - Jeffrey R Schriber; John J Freedman; Joseph M Brandwein (Canadian Journal of Infectious Diseases)
The first documented case of thrombotic thrombocytopenic purpura (TTP) associated with pneumococcal septicemia is reported. This association has been previously demonstrated with hemolytic uremic syndrome. The patient presented with recurrent seizures, oliguric renal failure, fever, thrombocytopenia and microangiopathic hemolytic anemia; coagulation studies were normal. Blood and sputum cultures were positive for Streptococcus pneumoniae. The patient responded to therapy with plasmapheresis and antiplatelet agents as well as antibiotics. Coincident infection should be searched for in all cases of TTP.